Penciptaan Karya Cetak Tinggi Aplikatif Dengan Inspirasi Candi Sewu - Sigit Purnomo Adi; Rohman (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This research is an art creation-based research that is different from art study-based research, which uses qualitative research methods and quantitative research. For this research, the art creation method is used, with a specialization in creating high-print works applied to tote bags, the urgency of the problem is very striking the use of bags made of plastic or better known as kresek bags which cause environmental pollution so that various alternatives appear to reduce it by using alternative canvas bags or better known as tote bags as alternative bags to replace plastic kresek bags. The solution to the problem uses canvas bags or known as tote bags with image designs inspired by the Sewu temple with high-print techniques. The goal is clear as an alternative media to replace plastic kresek bags in addition to being an alternative media for temple conservation, especially the Sewu temple by being used as inspiration for the creation of high-print techniques applied to tote bags, the method used is the Catur Cipta Karya art creation method. In conclusion, Sewu Temple in Yogyakarta served as a source of inspiration for creating applied graphic art, particularly for tote bags. The work combines artistic and aesthetic aspects for application on tote bags, a type of canvas bag that offers an alternative to plastic bags. The design was chosen using a high-density printing technique because high-density printing, in addition to its strong character, can also be an alternative to screen printing.